A method for determining local pulse wave velocity in human ascending aorta from sequential ultrasound measurements of diameter and velocity. (26th November 2018) - Negoita, Madalina; Hughes, Alun D; Parker, Kim H; Khir, Ashraf W
Abstract: Background : Pulse wave velocity (PWV) is an indicator of arterial stiffness, and predicts cardiovascular events independently of blood pressure. Currently, PWV is commonly measured by the foot-to-foot technique thus giving a global estimate of large arterial stiffness. However, and despite its importance, methods to measure the stiffness of the ascending aorta are limited. Objective : To introduce a method for calculating local PWV in the human ascending aorta using non-invasive ultrasound measurements of its diameter ( D ) and flow velocity ( U ). Approach : Ten participants (four females) were recruited from Brunel University students. Ascending aortic diameter and velocity were recorded with a GE Vivid E95 equipped with a 1.5–4.5 MHz phased array transducer using M-mode in the parasternal long axis view and pulse wave Doppler in the apical five chamber view respectively. Groups of six consecutive heartbeats were selected from each 20 s run based on the most similar cycle length resulting in three groups for D and three for U each with six waveforms. Each D waveform was paired with each U waveform to calculate PWV using ln( D ) U -loop method. Main results : The diastolic portions of the diameters or velocities waveforms were truncated to allow the pairs to have equal length and were used to construct ln( D ) U -loops. The trimmed average, excluding 10% of extreme values, resulting from the 324 loops was considered representative for each participant. Overall mean local PWV for all participants was 4.1(SD  =  0.9) m s −1 . Significance : Local PWV can be measured non-invasively in the ascending aorta using ultrasound measurements of diameter and flow velocity This should facilitate more widespread assessment of ascending aortic stiffness in larger studies.